Biosynthesis of Silver Nanoparticles using Rhizophora mucronata and Ceriops decandra and their Antagonistic Activity on Gut Cellulolytic Bacteria: Biosynthesis of Silver Nanoparticles using Rhizophora mucronata and Ceriops decandra and their Antagonistic Activity on Gut Cellulolytic Bacteria - Sankar, M. Vijaya (International Journal of Pharmaceutical & Biological Archive, 2019)
To find out the bactericidal properties of biosynthesis silver nanoparticles synthesized with Ceriops decandra (C. decandra) and Rhizophora mucronata (R. mucronata), aqueous leaf extract against the cellulolytic bacteria isolated from gut of Macrotermes convolsionarius a termite species. Further, characterization such as ultraviolet, X-ray diffraction (XRD), Fourier transform infrared (FT-IR), and scanning electron microscopy was analyzed for biosynthesized silver nanoparticles. A total of 16 isolates were collected from gut of termites. Of these, seven bacterial isolates exhibited positive cellulolytic test. The isolated cellulolytic bacterial colonies were subjected to antibacterial assay with synthesized silver nanoparticles of the selected mangrove plants. C. decandra showed highest zone of inhibition (16 mm at the concentration of 150 μg/disc) with TGBS15 and R. mucronata showed highest zone of inhibition (18 mm at the concentration of 150 μg/disc) with TGBS09. The synthesized silver nanoparticles of R. mucronata and C. decandra have maximum absorption at 430 and 400 nm. The XRD data showed 2 θ intense values with various degrees such as 25–30°. The FT-IR results revealed prominent peaks in R. mucronata showed absorption bands at 3444, 1622, 1384, 1071, and 471 cm−1 and C. decandra showed absorption bands at 3606, 3418, 2923, 1069, 474, and 426 cm−1, respectively. The biosynthesis of silver nanoparticles with aqueous leaf extract of R. mucronata provides potential source for cellulolytic bacteria of termites